A novel ultrasonic array signal processing scheme for wind measurement. (October 2018) - Li, Xinbo; Zhu, GeYan; Gao, Wei; Sun, Haixin; Liu, Guojun; Wu, Yue; Shi, Yaowu
Abstract: This article presents a novel ultrasonic array signal processing scheme for wind speed and wind direction measurement. Two ultrasonic array structures are illustrated and the corresponding array signal processing method is proposed. The statistical performance of proposed scheme, such as estimation variance and Cramer Rao Bound (CRB), is derived. The ambiguity problem for traditional uniform line array (ULA) structure is theoretically discussed. The hardware experiment results verify the feasibility of the proposed wind measurement method. Highlights: In this article, the reason why one arc array structure is employed rather than the traditional uniform line array (ULA) is elaborated. The statistical performance of proposed method, including estimate variance and Cramer Rao Bound (CRB) is derived. The hardware experimental platform is introduced and the corresponding measurement process for wind speed and wind direction is shown.